Local Electron-Lattice Interactions in High-Temperature Cuprate Superconductors - Hugo Keller; Annette Bussmann-Holder (Advances in Condensed Matter Physics)
Recent experimental observations of unconventional isotope effects, multiband superconductivity, and unusual local lattice responses are reviewed and shown to be naturally explained within a two-component scenario where local polaronic effects are important. It is concluded that purely electronic mechanisms of high-temperature superconductivity are incomplete and unable to capture the essential physics of cuprates and other layered superconductors.